Pelatihan Dalam Jaringan (Daring) Penulisan Artikel Ilmiah bagi Guru-guru MAN 3 Majalengka, Jawa Barat - Inu Isnaeni Sidiq; Nurul Hikmayati Saefullah; Rosaria Mita Amalia; Taufik Ampera; Erlina Zulkifli Mahmud; Nani Darmayanti (Jurnal Pengabdian Pada Masyarakat, 2021)
ONLINE TRAINING SCIENTIFIC ARTICLE WRITING FOR MAN TEACHERS 3 MAJALENGKA, WEST JAVA. Since February 2020, the Indonesian government has officially implemented a work from home policy in an effort to break the chain of the spread of the Covid 19 epidemic, which is also a problem facing all countries in the world. Even so, various tridarma activities of tertiary institutions must continue and covid 19 does not become an obstacle to remain productive. One form of tridarma of tertiary institutions that must be carried out is Community Service (PPM). The form of PPM carried out in the current epidemic situation is to utilize online technological assistance. Zoom communication media is conducted to provide training in writing scientific papers for MAN 3 Majalengka teachers. This training is needed by teachers who have been hampered by promotion because of difficulty in writing published scientific papers. The method used is lecture and training. The material provided in this training is the theory of language, selecting references, systematic scientific journals, and technical submission to national journals with accuracy. The result of this training is that participants can write a scientific work and can send it to reputable national journals.